Analisis Keterbukaan Ekonomi dan Pengeluaran Pemerintah terhadap Pertumbuhan Ekonomi Indonesia - Ikbar Allam Kharazi; Ida Nuraini (Universitas Nusantara PGRI Kediri, 2024)
The development success achieved by Indonesia to date cannot be separated from the existence of development plans that have been established and cooperation with other countries. The parameters for success can be seen from the value of gross domestic product (GDP), which continues to increase every year. The aim of this research is to determine the influence of foreign investment, government spending and foreign debt on economic growth in Indonesia in 2000-2022. This type of research is quantitative using secondary data which is time series sourced from the Indonesian Central Statistics Agency, the International Monetary Fund (IMF) and the World Bank. The analytical instrument used is multiple linear regression. The results of this research show that government spending has a significant impact on economic growth, while foreign investment and foreign debt do not have a significant impact on Indonesia's economic growth in 2000-2022.